EVALUASI PROGRAM DIKLAT ADMINISTRASI KEPEGAWAIAN PADA BALAI DIKLAT KEAGAMAAN KEMENTERIAN AGAMA JAKARTA (IMPLEMENTASI MODEL EVALUASI KIRKPATRICK) - Fahmy Zakiyuddin (Jurnal Evaluasi Pendidikan, 2016)
This research aims to evaluate the Administration Training and Education Program at Religious Training and Education Center in Jakarta. This study adopts a case study method with qualitative approach by using Kirkpatrick evaluation model that consists of reaction, learning, behavior, and result. The source of data consists of Program Coordinators, Heads and Employees of the said Work Unit, and the participants of the training who will be analyzed by using the interview, observation, and documentation instrument. The conclusion of this research are: 1) the reaction level has met the succes criteria, 2) learning level has met the succes criteria, 3) behavior level has not fully met the succes criteria, and 4) result level has met the succes criteria. The results showed that this DAK Program has, in general, met the succes criteria, but there are some aspects that need to be improved in order to achiveve the goals of the program.